Influence of microstructure and applied current on the electrical conductivity of SmBaCo2O5+d cathode in solid oxide fuel cell. (26th April 2022) - Song, Kyeong Eun; Lee, Jae Woong; Lim, Yu Ri; Baek, Seung Wook; Shin, Tae Ho; Lee, Shinku; Schlegl, Harald; Kim, Jung Hyun
Abstract: In this study, the electrical conductivity of SmBaCo2 O5+d (SBCO) is measured and analyzed with respect to the microstructure of the analyzed samples. The microstructure is influenced by the sintering temperature and by the precise composition of the composite cathode. Difference in the electrical conductivity at different applied current is investigated. The value of the electrical conductivity of SBCO sintered at 1150 °C was about 1024 S/cm at 600 °C, which was the highest compared to other samples sintered at lower temperatures. The electrical conductivities of porous microstructural SBCO sintered at 1150 °C with an addition of 10 wt% carbon black and of a composite cathode comprised of SBCO and Ce0.9 Gd0.1 O2 (CGO91) at a ratio of 1.9:0.1 were 256 and 525 S/cm at 600 °C. The electrical conductivities of SBCO samples increase when relatively low currents are applied. This trend can be observed at all pure SBCO and samples mixed with carbon black. However, these properties are not found in composite cathodes comprised of SBCO and CGO91. Highlights: The SBCO sample sintered at 1150 °C had the highest electrical conductivity. The lower the applied current, the greater the electrical conductivity. Composite samples showed decreased electrical conductivity compared to single phase SBCO samples.